Cartel Indications on Determination of Loan Interest Rate in Fintech Lending - Sukarmi Sukarmi; Ranitya Ganindha; Reka Dewantara (Yustisia, 2022)
The application of information technology platforms that appear in business transactions in Indonesia is a pattern of business models that cannot be avoided. One of the rapidly growing technology companies is an online loan service.The ease of borrowing funds through these services supports business growth. In contrast to the banking sector, which is regulated by a series of strict government regulations and the determination of interest rates that have been determined by looking at economic conditions. The absence of regulation in the legislation makes AFPI set the limit for determining the maximum interest rate, but the determination of interest rates by AFPI is suspected to lead to cartel actions. There is a close relationship between fair business competition and consumer protection. This research is a normative juridical research with a statutory approach and a comparative approach. In this case, the setting of interest rate limits will reduce consumers’ rights to get competitive prices. The existence of conscious parallelism by the AFPI on the LPMUBTI services can be categorized as a price fixing agreement. It is because the determination of the maximum interest rate limit is not regulated through direct government regulations.